2017
DOI: 10.1155/2017/3248605
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow Mesenchymal Stem Cells Inhibit the Function of Dendritic Cells by Secreting Galectin-1

Abstract: This study aimed to investigate whether bone marrow-derived mesenchymal stem cells (BM-MSCs) can inhibit function of dendritic cells (DCs) by secreting Galectin-1 (Gal-1). BM-MSCs have been shown to inhibit the maturation and function of DCs, further inhibiting the activation and proliferation of T cells. However, the detailed mechanism remains unknown. In this current study, MSCs and DCs derived from mouse bone marrow were cocultured using Transwell culture plates under different in vitro conditions. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 34 publications
0
23
0
Order By: Relevance
“…A recent study reports that MSCs secrete Galectin-1 and the authors postulate that this factor is able to inhibit dendritic cell function [ 25 ]. Furthermore, they detected increased Gal-1, IL-10, and IL-12 concentrations in supernatants from the co-culture system.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study reports that MSCs secrete Galectin-1 and the authors postulate that this factor is able to inhibit dendritic cell function [ 25 ]. Furthermore, they detected increased Gal-1, IL-10, and IL-12 concentrations in supernatants from the co-culture system.…”
Section: Discussionmentioning
confidence: 99%
“…TSG-6 also inhibits the maturation and function of DCs [164,165]. Zhang et al found that galectin-1 from MSCs stimulates the formation of a tolerance immunophenotype on DCs via regulating the MAPK signalling pathway in DCs, thereby inhibiting their function [166]. The immunomodulatory effects of MSC-derived factors have been observed during both the antigen recognition/ presentation stage and T cell activation stage of the immune response.…”
Section: Immunomodulatory Factorsmentioning
confidence: 99%
“…Firstly, galectin 1 seems to induce sorafenib-resistance in hepatocellular carcinoma through induction of αvβ3 integrin expression and activation of PI3K-Akt signaling [ 81 ]. Galectin-1 is also expressed in human AML bone marrow both by the leukemic cells and by stromal cells in the stem cell niches [ 82 , 83 ]. A recent study could not find any association between galectin expression in primary human AML cells and prognosis after conventional chemotherapy, but further studies are needed to clarify whether galectin-1 dependent chemoresistance is important for subsets of patients or for kinase inhibitory strategies.…”
Section: Summarizing and Concluding Commentsmentioning
confidence: 99%